An analysis of competency, needs, and gap on Thai engineering capabilities within ASEAN - Duangporn Kraisuth; Sudaporn Sawmong (My University, 2018)
Just two nations in Southeast Asia have committed to programs and funding to prepare over 72,000 new PhD researchers and academics for specific industries. This study, therefore, conducted both a quantitative and qualitative analysis of 412 Thai engineers selected from a population of 1211 Thai Federation of Industries companies to investigate how need, gap, and competency affected Thai engineer work capability. The structural equation model was conducted with AMOS 21 software and from the analysis, competency (β = 0.16) and needs (β = 0.77) demonstrated a significant effect on capabilities, while needs demonstrated a significant effect on the gap. Additionally, cultural awareness of other Asian regional nations ranked as the weakest link in an engineer's capability perception.
Keywords: Human Resource and Talent Management